Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Pelanggan Kikim Variasi Mobil Yogyakarta - Muhammad Irfan Fathurrahman; Agus Abdurrahman (Journal of Management and Creative Business, 2024)
The purpose of this study was to analyze (1) the effect of service quality on customer satisfaction, (2) the effect of pricing on customer satisfaction, (3) the effect of service quality and price on customer satisfaction. This type of research is quantitative with Kikim Variasi Mobil customer respondents totaling 96 respondents selected using Hair et al. calculations (2010). Data analysis using multiple linear regression analysis with the IBM SPSS Statistic 22 test tool. The results showed that (1) service quality has a positive and significant effect on customer satisfaction of Kikim Variasi Mobil Yogyakarta. (2) Pricing has a positive and significant effect on customer satisfaction of Kikim Variasi Mobil Yogyakarta. (3) Service quality and pricing together have a significant effect on customer satisfaction of Kikim Variasi Mobil Yogyakarta.